Influência do tratamento dentinário com Clorexidina, Ácido Hialurônico ou Vitamina C na resistência adesiva e propriedades mecânicas da camada híbrida - Silva, Patricia Rondon Pleffken da [UNESP] (2013)
The aim of this study was to evaluate the influence of chlorhexidine, hyaluronic acid and C vitamin C on dentin bond strength and on the hybrid layer mechanical properties. The buccal surface of ninety six extracted bovine teeth was ground to exposure a flat dentin surface. The specimens were divided in four experimental groups (n=24): G1 (Control) - application of the adhesive system (Adper Single Bond 2); G2: dentin treatment with chlorhexidine 2% for 1 min + adhesive system; G3: dentin treatment with hyaluronic acid 1% for 1 min + adhesive system; G4: dentin treatment with C vitamin 10% for 1 min + adhesive system. After polymerization of the adhesive system, two increments of the composite resin, Filtek Z 350 (3M ESPE), were placed on dentin with the aid of a matrix and polymerized for 20 s each. The specimens were stored in distilled water at 37ºC for 24 h (n=12) and 6 months (n=12). They were then sectioned in order to obtain specimens with an area of approximately 1 mm2. They were submitted to microtensile bond strength tests using a universal testing machine (DL- 1000, EMIC/10 kgf/ 0,5 mm/min). One specimen of each of the groups stored for 6 months was submitted to nanohardness and elasticity module tests for the hybrid layer. Data were analyzed by two-way ANOVA and Tukey's test. Tests performed after 24 h showed higher adhesive bond strength for groups G1, G2 and G3, but after six months the highest values were presented by groups G2 and G3. Nanohardness tests revealed greater resistance for G3 compared to the other groups. Modulus of elasticity was found to be the same for all groups. It could be concluded that the application of chlorhexidine and hyaluronic acid on dentin was effective in keeping high bond strength values after 6 months but regarding the hybrid layer only hyaluronic acid increased nanohardness